Amoebic dysentery - Marie, Chelsea (BMJ Publishing Group, 2013)
INTRODUCTION: Amoebic dysentery is caused by the protozoan parasite Entamoeba histolytica. It is transmitted in areas where poor sanitation allows contamination of drinking water and food with faeces. In these areas, up to 40% of people with diarrhoea may have amoebic dysentery. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical question: What are the effects of drug treatments for amoebic dysentery in endemic areas? We searched: Medline, Embase, The Cochrane Library, and other important databases up to June 2013 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 6 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: diiodohydroxyquinoline (iodoquinol), diloxanide, emetine, metronidazole, nitazoxanide, ornidazole, paromomycin, secnidazole, and tinidazole.